Menjadi Lesbian: Kajian Interaksionisme Simbolik Lesbian di Surabaya - Wiwid Megananda (Universitas Trunojoyo Madura, 2019)
This article is entitled Becoming Lesbians: A Symbolic Interactionism Study of Lesbian Identity (Case Study in the City of Surabaya). Researchers focus on lesbian individuals not on the lesbian community. The problem raised by the researcher is how the whole process of choosing someone to be a lesbian and the symbols used for interaction with other lesbians. The purpose of this study is to know how a person chooses his life as a lesbian and to find out the symbols used to interact with lesbians. The method used is a qualitative method with a phenomenological approach. In this study informants numbered four people and all four occupy their respective roles in lesbians. From the results of this study there are several reasons why someone chooses to become a lesbian: social profiles, her-story, lesbian firts time, what changes, reactions and what next. From these concepts, the conclusion is that family background does not influence a person to become a lesbian, but rather from personal experiences in the past or experiences with social relations.